The impacts of oil price shocks on the stock market index of the ASEAN-4 countries from January 2012 to October 2022: An analysis - Banzon, Miguel Enrico V. (Animo Repository, 2023)
The study aims at analyzing how the price of oil impacts the stock market index of the ASEAN-4 countries principally, the Philippines, Indonesia, Malaysia, and Thailand from January 2012 to October 2022. The data In the research procedure was gathered from Refinitiv Eikon Database. In the study, the oil price shocks will be decomposed into three structural shocks which are, oil supply shock, aggregate demand shock, and oil-specific demand shock. To know how these structural shocks impact the stock market index for the ASEAN-4 Countries, the study will be utilizing the Structural Vector Autoregressive model (SVAR) to examine the impacts of the structural shocks. Furthermore, the study also analyzes the implications of an increase in the price of oil during bear markets and as well as bull markets with the help of the Threshold Structural Autoregressive model (TSVAR). The results of the TSVAR and SVAR models illustrated that oil supply shock was not seen any influence on the Philippines, Thailand, and Indonesia. However, Malaysia was significantly impacted by the oil supply shock during the bull market. Aggregate demand shock was not able to impact the stock market index for the Philippines, Thailand, Malaysia, and Indonesia. Lastly, oil-specific demand shock was also not seen any significant impact on the ASEAN-4 stock market index.